ANALISIS SWOT MANAJEMEN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH MUHAMMADIYAH SIDOKERTO PLUPUH SRAGEN - Isnaini, Isnaini; Halimah, Siti; Narimo, Sabar; Anif, Sofyan (STKIP Pesisir Selatan, 2026)
Improving quality in Islamic primary schools requires a headmaster who can strategically interpret internal and external conditions. This paper aims to map strengths, weaknesses, opportunities, and threats in educational quality management at Madrasah Ibtidaiyah Muhammadiyah Sidokerto Plupuh Sragen and to formulate feasible quality-improvement strategies centered on headmaster leadership. The method is a literature study using content analysis of recent scholarly works and relevant documents, synthesized through the SWOT framework and the TOWS matrix. The main findings indicate that internal strengths are generally driven by religious culture, organizational networks, and leadership potential to cultivate a quality culture, while weaknesses often relate to inconsistent internal quality assurance practices, uneven teacher competence development, and limited resources to sustain innovation. External opportunities include strengthening parent–community partnerships, expanding digital learning literacy, and improving program planning based on quality indicators; key threats stem from competition among similar institutions, rising service expectations, and the risk of innovation stagnation.